Diagnostic Accuracy of Multi-detector Computed Tomography in the Evaluation of Non-traumatic Acute Abdominal and Pelvic Emergencies: A Cross-sectional Study - R Mohan Kumar; Anupam Jhobta; Sumala Kapila; Shruti Thakur; Sushma Makhaik; Neeti Aggarwal; Charu S Thakur (International Journal of Anatomy Radiology and Surgery, 2024)
Introduction: Acute abdomen can sometimes be life-threatening and requires an exact diagnosis and appropriate management to avoid mortality among patients. Multi-detector Computed Tomography (MDCT) provides a specific diagnosis and the whole picture of pathology, especially in patients with inconclusive diagnoses. Aim: To evaluate the accuracy of MDCT in diagnosing non-traumatic acute abdominal and pelvic emergencies. Materials and Methods: A cross-sectional study was conducted on 100 patients who presented with acute abdomen and had inconclusive diagnoses based on clinical examination, laboratory investigations, and other imaging modalities. MDCT was performed with a specific protocol depending on the clinical diagnosis. The MDCT results were compared with intraoperative findings, clinical recovery, and Histopathological Examinations (HPE). Data was entered into a Microsoft Excel spreadsheet and analysed using Statistical Package for Social Sciences (SPSS) version 20.0. Results: The MDCT diagnosis was concordant in 95% of patients and discordant in 5% of patients. Acute appendicitis was the most common cause of acute abdomen (20%). Overall sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of MDCT in diagnosing the aetiology of acute abdomen were 96.49% (CI 87.89% to 99.57%), 97.67% (CI 87.71% to 99.94%), 98.21% (CI 90.45% to 99.95%), 95.45% (CI 84.53% to 99.44%), and 97%, respectively. Conclusion: Since the clinical findings overlap in patients with acute abdomen, making an accurate clinical diagnosis is challenging. In these cases, MDCT provides a diagnosis with high accuracy and specificity in a short duration of time; hence, MDCT should be performed in acute abdominal emergencies for appropriate patient management.